2022
DOI: 10.3390/en15155712
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Distribution of Coal-Measure Source Rocks in Mixed Platform: A Case Study of Carboniferous in Bamai Area, Southwest Tarim Basin, China

Abstract: Coal-measure source rocks are generally developed in marsh facies under a humid climate and are rarely reported in a carbonate platform or a mixed platform. Carboniferous seawater intruded from west to east in the Tarim Basin, and mixed platform deposits of interbedded mudstone and carbonate developed in the southwest of the basin. In recent years, with the deepening of the exploration, nearly 20 m coal seams and carbonaceous mudstone source rocks have been found in the Carboniferous lagoon’s tidal-flat backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Duncan argued that coal measure source rock plays an indispensable role in gas generation. According to the research, coal measure source rock could even have a special type of "self-generation and self-storage" capacity according to a geochemical characteristic comparison [11][12][13][14]. With the help of further research, coal-formed gas has increasingly been found in various basins [7,15,16] and by researchers who are simultaneously working on the factors that limit the petroleum potential of coal measure source rock [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Duncan argued that coal measure source rock plays an indispensable role in gas generation. According to the research, coal measure source rock could even have a special type of "self-generation and self-storage" capacity according to a geochemical characteristic comparison [11][12][13][14]. With the help of further research, coal-formed gas has increasingly been found in various basins [7,15,16] and by researchers who are simultaneously working on the factors that limit the petroleum potential of coal measure source rock [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%